Guidelines for defining user requirement specifications (URS) of manufacturing execution system (MES) based on ISA-95 standard. Issue 3 (February 2019) - Yue, Lei; Niu, Pengfei; Wang, Yan
Abstract: To standardize the authoring of user requirement specifications (URS) for manufacturing execution system (MES) proposed by manufacturing enterprises from users' perspectives, and facilitate a quick and effective communication between them and MES vendor or integrator, an approach for URS definition was introduced based on the ISA-95 standard, in which a method for requirement elicitation based on goal and scenario was combined. In this approach, a framework for MES problem space was constructed first from three dimensions: generic activity model for manufacturing operations management (MOM), manufacturing operations categories and supporting activities, and then a series of guidelines for standard application, scenario authoring and requirement arrangement were established to guide the users in seeking the needs and writing them in a normalized sentence form step by step. Additionally, a structure of the table of content for URS documentation was recommended to help the users organizing the textual requirement description. Finally, a case study for applying this approach was performed in a pharmaceutical company's example, which illustrates the application prospect in MES product selection.